Reconsidering Nigeriaâ€™s Role in the Southern African Struggles* (Journal of Management and Social Sciences, 2020)
This paper examines xenophobic attacks on Nigerian nationals living in post-apartheid South African in spite of Nigeriaâ€™s significant contributions to the Southern African struggles for majority rule.â€œWe shall endeavour to remain on friendly terms with every nation which recognises and respects our sovereignty, and we shall not blindly follow the lead of anyone. So far as is possible, the policy for each occasion will be selected with a proper independent objectivity in Nigeriaâ€™s national interest. We consider it wrong for the Federal Government to associate itself, as a matter of routine, with any of the power blocs. This freedom of action will be an essential feature of our policy founded on Nigeriaâ€™s interest and will be consistent with the moral and democratic principles on which our Constitution is based." Sir Abubakar Tafawa Balewa, â€œA Policy for Foreign Affairs,â€ August 10, 1960, Lagos1.â€œIt is the desire of Nigeria to remain on friendly terms with all nations and to participate actively in the work of the United Nations Organisation. Nigeria, a large and populous country has absolutely no territorial or expansionist intentions. We shall not forget our old friends and we are proud to have been accepted as a member of the Commonwealth, but we do not intend to align ourselves as a matter of routine with any of the power blocs. We are committed to uphold the principles upon which the United Nations Organisation is founded. Nigeria hopes to work with other African states for the progress of Africa and to assist in bringing all African territories to a state of responsible independence. Sir Abubakar Tafawa Balewa, â€œSovereign Nigeria and the World.â€, October 8, 1960, New York2